A simple manufacturing process of the miniaturised octopus-inspired underwater soft robotic grippers. Issue 7 (3rd April 2023) - Eroğlu, Murat; Şam Parmak, Ebru Devrim
Abstract: In this article, we show a new fabrication technique based on CNC machining for the miniaturised octopus-inspired underwater soft robotic grippers. This method provides practical and scale-up production of these grippers. Polydimethylsiloxane/polyethylene terephthalate (PDMS/PET) film (∼7 × 7 cm 2 ) consisting of concave structures in two different geometries (outer and inner) with the suction-based property was produced by using our suggested manufacturing method. The highest adhesion force was obtained on the flat deformable object by the outer concave structured gripper (∼6 kPa) and the flat rigid object by the inner concave structured gripper (∼12 kPa). Moreover, both the grippers exhibit switchable adhesion by changing the retraction velocity as well as high repeatability (over 100 cycles) in underwater conditions. This method will enable practical fabrication of the miniaturised octopus-inspired underwater soft robotic grippers. The proposed manufacturing technique will facilitate the widespread use and commercialisation of the grippers.